1998
DOI: 10.7326/0003-4819-128-1-199801010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Famciclovir for the Suppression of Symptomatic and Asymptomatic Herpes Simplex Virus Reactivation in HIV-Infected Persons: A Double-Blind, Placebo-Controlled Trial

Abstract: Antiviral chemotherapy with famciclovir results in clinically and statistically significant reductions in the symptoms associated with HSV infection and the symptomatic and asymptomatic shedding of HSV among HIV-positive persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(63 citation statements)
references
References 26 publications
1
61
0
1
Order By: Relevance
“…Clinical trials have shown that FCV is effective in the treatment of acute herpes labialis and genital herpes (39,41) and as a prophylactic treatment of UV-induced herpes labialis, excimer laser skin resurfacing, and genital herpes (2,11,43,44). We report that FCV may be beneficial in reducing corneal morbidity in patients with recurrent herpes keratitis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Clinical trials have shown that FCV is effective in the treatment of acute herpes labialis and genital herpes (39,41) and as a prophylactic treatment of UV-induced herpes labialis, excimer laser skin resurfacing, and genital herpes (2,11,43,44). We report that FCV may be beneficial in reducing corneal morbidity in patients with recurrent herpes keratitis.…”
Section: Discussionmentioning
confidence: 85%
“…FCV is currently approved for the treatment of herpes zoster and the treatment and suppression of genital herpes (7,9). FCV has also been used in clinical trials for herpes labialis (2,8,11,39,41,43,44). A clinical trial by Spruance et al (44) demonstrated that oral FCV decreased the median lesion size in a dose-dependent manner and that, at higher doses, it decreased the time to healing following UV radiation-induced HSV labialis.…”
mentioning
confidence: 99%
“…There is evidence of more rapid HIV-1 disease progression in dually infected individuals (6,15,29) as well as in vitro data demonstrating that HSV-2 proteins can activate the HIV-1 long terminal repeat, leading to increased HIV-1 replication (10,18,23). Recent trials of acyclovir monotherapy for HSV-2 infection in HSV-2/HIV-1-coinfected individuals showed an approximately 0.33 to 0.5 log 10 decrease in HIV-1 plasma levels, but the overall benefits of this approach remain unclear (24,30,36).…”
mentioning
confidence: 99%
“…재발방지에 효과있는 약제로 경구 acyclovir, valacyclovir, famciclovir가 있다(AI) [246][247]. 이 경우 HIV 감염인 에서는 valacyclovir를 하루 두번 500 mg 투여한다(AI).…”
Section: ) 재발의 방지unclassified